Economic integration, regional structural change and cohesion in the EU new member-states - Dimitris Kallioras; George Petrakos; Georgios Fotopoulos (European Regional Science Association (ERSA), 2005)
The European economic landscape has changed dramatically during the last decade, following the collapse of the bi-polar world. The parallel and interacting processes of economic integration and transition are the driving forces of these changes. In this context, the EU new member-states (including the candidate countries of Bulgaria and Romania) have experienced, often forcefully and painfully, the impact of these processes as a pre-condition for catch-up and integration with the prosperous EU-15 countries. Being still in progress, these processes have altered the intraregional division of labor, affecting the patterns of regional specialization and industrial concentration and increasing the level of interregional competition and inequalities, in a newly emerged internationalized environment. The extent and the impact of these changes, however, are still issues of major scientific dialogue and concern, with many unknown parameters. The need for this first period of transition and economic integration (decade of 90s) to be re-evaluated is evident concerning the mobility of economic activities and possible re-location of industries, the behaviour of the individual regions, the dynamics of regional discrepancies and the stability of the territorial structures. The overall scientific objective of this paper is to identify and explain in a cross-country and comparative analysis the structural industrial patterns in the area of EU new member-states bringing together the findings and reports of the scientific bibliography. Furthermore, a static and dynamic analysis takes place in order to uncover in more depth the possible relation between economic integration, regional structural change and cohesion in these countries. To this direction, a number of research questions are addressed: What is the impact of economic integration to the evolution of regional industrial patterns? Have advanced and lagging-behind regions developed similar or different types of specialization? What is their mix of activities? Over time, do they become more similar or dissimilar? Have metropolitan regions the same mix of activities with peripheral and border regions? Do their economic structures become more similar or dissimilar over time? Are there particular types of structural change more closely related to strong growth performance? The main part of the analysis is conducted on a basis of employment data, as a proxy for industrial structures in NUTS III spatial level, disaggregated by manufacturing branches according to NACE rev.1 two-digit classification. Emphasis is given to the countries of Bulgaria, Romania, Slovenia, Hungary and Estonia due to lack of statistical information (regional-structural figures) for the other countries under research. However, despite this shortcoming, the country sample of our analysis can be considered representative of the whole area since it covers all its parts i.e. Southeastern Europe–Balkans (Bulgaria, Romania), Central Europe (Slovenia, Hungary), Eastern Europe–Baltic (Estonia). The research covers the period between 1990 and 1999, a period of extreme significance since it includes both the shocks and the upsets of the early transition (sub-period 1991–1995) and the recent, more independent, trends (1995–1999). The reported findings and conclusions of this research may be a valuable basis for the understanding of the impact of economic integration on regional structure change and cohesion and, as a result, be the basis for the discussion of the appropriate policies of cohesion in the enlarged EU-27.
Keywords: 330